2014
DOI: 10.1590/s0100-7203201400050004
|View full text |Cite
|
Sign up to set email alerts
|

PTEN expression in patients with carcinoma of the cervix and its association with p53, Ki-67 and CD31

Abstract: PURPOSE: To investigate protein expression and mutations in phosphatase and tensin homolog (PTEN) in patients with stage IB cervical squamous cell carcinoma (CSCC) and the association with clinical-pathologic features, tumor p53 expression, cell proliferation and angiogenesis. METHODS: Women with stage IB CSCC (n=20 -Study Group) and uterine myoma (n=20 -Control Group), aged 49.1±1.7 years (mean±standard deviation, range 27-78 years), were prospectively evaluated. Patients with cervical cancer were submitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Besides that, the current study found that loss of PTEN expression and overexpression of PI3K was associated with clinical stage of cervical cancer (stage II and III respectively). Qiufeng et al 61 and Loures et al 62 revealed that loss of PTEN expression plays an important role in the multiple steps of tumorigenesis and progression of cervical squamous cell carcinoma, which is consistence with our results. Real-time PCR results showed that mRNA expression levels were significantly elevated, which also correlates with IHC findings of overexpression of NF-kB, COX-2, PI3K, and loss expression of PTEN in cervical squamous tissues compared to non-tumor tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Besides that, the current study found that loss of PTEN expression and overexpression of PI3K was associated with clinical stage of cervical cancer (stage II and III respectively). Qiufeng et al 61 and Loures et al 62 revealed that loss of PTEN expression plays an important role in the multiple steps of tumorigenesis and progression of cervical squamous cell carcinoma, which is consistence with our results. Real-time PCR results showed that mRNA expression levels were significantly elevated, which also correlates with IHC findings of overexpression of NF-kB, COX-2, PI3K, and loss expression of PTEN in cervical squamous tissues compared to non-tumor tissue.…”
Section: Discussionsupporting
confidence: 93%
“…More importantly, it has been confirmed that PTEN, which counteracts PI3K/Akt activity, is involved in various aspects of cancer development, such as inhibition of cell proliferation, apoptosis, migration and invasion (8,44,45). In particular, PTEN expression intensity is lower in cervical cancer than benign cervical samples (46) and a decreased expression of PTEN was found in invasive cervical cancers (47). From the previous study, we concluded that the PTEN/PI3K/Akt signaling pathway is important in the carcinogenesis and development of cervical cancer, thus identifying the molecules regulating PTEN/PI3K/Akt may be an attractive strategy for the underlying mechanism of cervical carcinogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…The absence of expression of this tumor suppressor protein is consistent with tumor progression.The present results are close to Lee et al [22] who detected that PTEN staining was inversely correlated to grade of differentiation and also with tumor stage. Different results by Loures et al [23] who found no associations between tumor PTEN expression and tumor stage, grade of differentiation or pelvic lymph node metastasis in CSCC cases, these contradictions may be due to selection of their studied cases which are mostly low grade lesions. Other contradictory results by Bertelsen et al [14] reported that PTEN is clearly positive in all tumor tissues including the mutated metastatic tumor.…”
Section: Discussionmentioning
confidence: 63%